PATRIMOINE ET DEVELOPPEMENT DURABLE DANS LE CONTEXTE ALGERIEN:UNE DUALITE COMPLEMENTAIRE OU OPPOSEE ? - BENABBAS, M.; DJAGHROURI, D.; AFREN, R. (Courrier du Savoir, 2017)
ABSTRACT Heritage and sustainable development are two notions that present certain correspondences, which express the desire to better integrate the temporal dimension, to better explore the past, the present and the future of societies, in logic of transmission and solidarity interlining. The concept of "heritage" is born a particular object to become an integral part of a set often linked to a space. Thus, the concept is constantly evolving and expanding with new dimensions (prehistoric, environmental, geographical, etc.). Algeria has a varied culture and a rich cultural and natural heritage, rare by its historical and symbolic significance, confirming the passage of several civilizations. However, identifying the sites to be classified remains an arduous task because of the values that can be at the origin of this scheduling. Another measure, in response to this procedural shortcoming to ensure the protection and enhancement of the heritage, legislation has emerged specifying the conditions of intervention on historic places and buildings and despite the problems and urban realities, heritage has never been subjected to general debates, as is done elsewhere, especially in the developed countries, where all actions undertaken on heritage contribute to sustainable development. Despite its overwhelming importance for society and the wide-ranging investigation of its broad capacities to contribute to the objectives of the three pillars of sustainable development (social, economic and environmental), in relation to the Algerian context, the question arises as to the interest of the heritage with regard to sustainable development. In order to answer this question, we will try to explore the world heritage which can provide a platform to develop and test new approaches that demonstrate the relevance of heritage for sustainable development.